Effect of Ashwagandharista (Withania somnifera) on the kidney functions of male and female rats (Jahangirnagar University Journal of Biological Sciences, 2019)
The key objective of this present study was to analyze the effect(s) of Ashwagandharishta on the kidney functions of both male and female Albino rats. Chronic toxicity tests were also done. Following treatments the rats were observed for 51 days to know the effects of Ashwagandharishta on kidney functions considering 3 parameters such as serum urea, creatinine and uric acid. Our results failed to exhibit a significant increase in serum urea level at low dose (P